Improving tuberculosis control through public-private collaboration in India: literature review. Issue 7541 (8th February 2006) - Dewan, Puneet K; Lal, S S; Lonnroth, Knut; Wares, Fraser; Uplekar, Mukund; Sahu, Suvanand; Granich, Reuben; Chauhan, Lakhbir Singh
Abstract: Objective To review the characteristics of public-private mix projects in India and their effect on case notification and treatment outcomes for tuberculosis. Design Literature review. Data sources Review of surveillance records from Indian tuberculosis programme project, evaluation reports, and medical literature for public-private mix projects in India. Data extraction Project characteristics, tuberculosis case notification of new patients with sputum smear results positive for acid fast bacilli, and treatment outcome. Data synthesis Of 24 identified public-private mix projects, data were available from 14 (58%), involving private practitioners, corporations, and non-governmental organisations. In all reviewed projects, the public sector tuberculosis programme provided training and supervision of private providers. Among the five projects with available data on historical controls, case notification rates were higher after implementation of a public-private mix project. Among seven projects involving private practitioners, 2796 of 12 147 (23%) new patients positive for acid fast bacilli were attributed to private providers. Corporate based and non-governmental organisations served as the main source for tuberculosis programme services in seven project areas, detecting 9967 new patients positive for acid fast bacilli. In nine of 12 projects with data on treatment outcomes, private providers exceeded the programme target of 85% treatment success for new patients positive for acid fast bacilli. Conclusions Public-private mix activities were associated with increased case notification, while maintaining acceptable treatment outcomes. Collaborations between public and private providers of health care hold considerable potential to improve tuberculosis control in India.